Characteristics of longwave radiation through the statistical analysis of downward and upward longwave radiation and inter-comparison of two sites in Cyprus. (November 2017) - Pashiardis, S.; Kalogirou, S.A.; Pelengaris, A.
Abstract: In this study, three years of hourly longwave downward and upward irradiance measurements for two sites in Cyprus representing two different climate regimes (inland vs coastal locations) are used to analyse and compare them. The quality control process was based on physically possible, extremely rare and climatological limits. Furthermore, comparison tests between the two longwave components as well as with air and ground surface temperatures were used to evaluate the hourly values of longwave irradiances. The annual mean daily downward longwave irradiation at Athalassa is 29.1 MJ m −2 and at Larnaca it is slightly higher (31.3 MJ m −2 ). On the other hand, the annual mean daily upward longwave irradiation at Athalassa is 38.2 MJ m −2, while at Larnaca it is slightly lower (37.4 MJ m −2 ). The performance of various models in estimating the daylight downward and upward longwave irradiances under clear-sky and all-sky conditions was evaluated. Root-mean-square errors, mean bias errors, and linear regression correlations have been used to compare measured and estimated values. The results of this comparison for the station of Athalassa, showed that Idso's model perform well and it can be used to estimate downward longwave irradiance under clear-sky conditions. Furthermore, Idso's model was extended to estimate the daylight downward longwave irradiance under all-sky conditions by taking into account the ratio of global to the clear-sky global solar irradiance. The RMSE of the local calibrated coefficients scheme of Idso's model was 17.70 W m −2 . For the estimation of the daylight upward longwave irradiance under all-sky conditions, the calibrated Dognieux and Lemoine model was used which performed well. The RMSE in this case was 12.75 W m −2 . Highlights: Quality control processes of longwave radiation components. Statistical analysis of downward and upward longwave radiation. Statistical relationships of hourly and daily longwave radiation values. Modelling longwave radiation components under clear-sky and all-sky conditions. Comparison of the longwave radiation between two sites.